International trade, welfare, and the theory of general equilibrium - Marjit, Sugata, 1959-; Kar, Saibal (New Delhi, India : Cambridge University Press, 2018)
This essential volume reflects the continuing and enduring utility of general equilibrium as a framework of analyses. It attempts to reiterate that understanding broad and holistic consequence of economic events and policies go beyond partial equilibrium perspective. Cutting across areas of research, general equilibrium perspectives in terms of small-scale GE models following the theory and perspectives of Ronald Jones can help readers develop informed judgement regarding critical policies. These include but are not limited to several areas of specific interest - the interaction of financial factors with international trade and implications for the 'real sectors' of the economy, the impact of labour market reforms on the unorganised sectors in developing and transition countries, the non-uniform effects of inflation and deflation on internal and external factor flows, and the sought-after relation between foreign investment and skill accumulation.
Title from publisher's bibliographic system (viewed on 16 Nov 2018).
Keywords: Equilibrium (Economics); International trade; Welfare economics